I'm a boy anorexic - Arce, Alicia ([S.l.] : BBC Active, 2006)
This programs provides information on Anorexic among boys. explain how boys get anorexia, how does it differ from the way girls get, and does it play out differently for boys. The boys' personal battle and queast for answers is touching and full of discovery. Will society's obsession with thin provide some truths or is the solution closer to home
Title from title screen
Executive producer, David Belton, Lucy Itefherington ; film editord, Jules Cornell, Dave Richards, Graham Taylor
Narrated by Ralf Little
DVD Format
Keywords: Anorexia nervosa